Exploring The Suitability Between GIATMARA and SBEZ’s Development Towards TVET Training - Ishak, Nor Syahidah; Sohaimi, Nor Suzylah; Abdullah, Fikriyah; Wan Saleh, Wan Shamsul Rezal (Journal of Technical Education and Training, 2023)
This study investigates and explore how community involvement and engagement through TVET at Special Boarder Economic Zone (SBEZ), Bukit Kayu Hitam through collaboration with one of the TVET educational providers namely GIATMARA. With the tertiary education and skill-based programmes, young community at SBEZ will have a better opportunity for employability and able to meet the demand from industry. This study employs a qualitative method with the information on the course offered by GIATMARA, the demand skills and from SBEZ development and the readiness of the community towards TVET skills around that area. The depth and breadth of the data collected through semi-structure interview with Northern Gateway, GIATMARA and SBEZ community. Building on the analysis, thematic analyses were then undertaken on the data from interviews. In particular, to ensure the successful of SBEZ, the surrounding community needs to be equipped with TVET skills especially related to logistic nd supply chain industry. Further, there are nine are of services of logistic and supply chain that are expected to be fulfilled for upcoming demand in SBEZ. It is hope that all TVET institutions including GIATMARA have to ensure that their curriculums are in line with the needs of the industry.